Własny ojciec - autorytet czy anty-wzór? O rodzicielskich wzorcach wśród młodych ojców = One`s own father: an authority or an anti-model? On parental patterns among young fathers - Bierca, Marta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article deals with the problem of parental authorities as understood by young men who become fathers themselves and define themselves as committed parents. The inspiration to undertake this subject emerged from the theme of the reserved, cool, strict or even totally absent father, which appears in the biographical discourse of respondents.
Keywords: socjologia rodziny; męskość; ojcostwo; zmiana społeczna; władza; sociology of family; masculinity; fatherhood; social change; authority